Studies in Indian planning and economic policy - Sinha, R. K. (Raj Kishore), 1946- (New Delhi : Deep & Deep Publications, 1984)
Contributed articles.
Includes index.
Bibliography: p. [466]-468.
Keywords: India -- Economic policy -- 1947-